RESTART Sustainable Business Model Innovation - Jørgensen, Sveinung (Palgrave Studies in Sustainable Business In Association with Future Earth,, 2018)
Taking the business model as point of departure, this open access book explores how companies and organizations can contribute to a more sustainable future by designing innovative models that are both sustainable and profitable. Based upon years of research, it draws together theoretical foundations and existing literature on the topic of sustainable business alongside case studies and practical solutions. After examining the theoretical foundations of sustainable business model innovation, the authors present their own framework - RESTART. Consisting of seven factors, this framework can be the basis for restarting any business model. The final section outlines a research agenda for sustainable business informed by the perspectives and frameworks put forward in this book.